2014
DOI: 10.1080/10962247.2014.882282
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-density polyethylene on smoke emissions from burning of simulated debris piles

Abstract: Low-density polyethylene (LDPE) plastic is used to keep piled debris from silvicultural activities-activities associated with development and care of forests-dry to enable efficient disposal by burning. The effects of inclusion of LDPE in this manner on smoke emissions are not well known. In a combustion laboratory experiment, 2-kg mixtures of LDPE and manzanita (Arctostaphylos sp.) wood containing 0, 0.25, and 2.5% LDPE by mass were burned. Gaseous and particulate emissions were sampled in real time during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Naphthalene has been detected (via GC-MS) in tars that were condensed from gas-phase pyrolysis products of both live and dead southeastern fuels, such as live oak (Quercus virginiana) and swamp bay (Persea palustris) (Safdari et al, 2018). It has also been detected (Koss et al, 2018;Hosseini et al, 2014;Aurell et al, 2017) in the gas phase in laboratory burning experiments. The detection of gas-phase naphthalene from wildland fire emissions is thus not surprising, but this is the first report of its identification via IR spectroscopy.…”
Section: Naphthalenementioning
confidence: 99%
“…Naphthalene has been detected (via GC-MS) in tars that were condensed from gas-phase pyrolysis products of both live and dead southeastern fuels, such as live oak (Quercus virginiana) and swamp bay (Persea palustris) (Safdari et al, 2018). It has also been detected (Koss et al, 2018;Hosseini et al, 2014;Aurell et al, 2017) in the gas phase in laboratory burning experiments. The detection of gas-phase naphthalene from wildland fire emissions is thus not surprising, but this is the first report of its identification via IR spectroscopy.…”
Section: Naphthalenementioning
confidence: 99%
“…PE also contributes to significant changes in CO emissions when incinerated together with agricultural byproducts. Hosseini et al (2014) reported that when a mixed specimen of manzanita (Arctostaphylos sp. ), which is native to North America, and LDPE was incinerated, the CO emission factor was different depending on the LDPE content, but also that the PE had an effect on the increase in combustion efficiency, so further statistical review would be needed.…”
mentioning
confidence: 99%
“…A Pitot tube (Testo 0635 2145, Testo Korea Ltd, Seoul, Korea) was inserted into the velocity traverse port and connected to an analyzer box (Testo 350k, Testo Korea Ltd, Seoul, Korea) to measure the wind speed by the differential pressure. In this infrastructure, the heat generated during combustion is naturally cooled through the duct, and the gas temperature of the velocity traverse port is set to be maintained at an average of less than 100 • C. The particulate pollutants generated in the flame, mixed combustion stage and the soot stage, were collected from the duct [44]. Particulate matter sampling was conducted at a wind speed of 1.75 Âą 0.37 m 3 /min.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In order to secure the reliability of EDS-based chemical species analysis, a verified standard sample [7] (Micro-Analysis Consultants LTD) was used to conduct the spectral location standard and quantification calibration. and the soot stage, were collected from the duct [44]. Particulate matter sampling was conducted at a wind speed of 1.75 Âą 0.37 m 3 /min.…”
Section: Experimental Methodsmentioning
confidence: 99%